Strategic Planning for Operation of Large Hydropower Plants - Awasthi, Shambhu Ratan; Prasad, Vishnu; Rangnekar, Saroj (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Electricity is an integral part of modern life. The main sources of power generation continue to be the fossil fuels which are largely responsible for global warming. In view of environmental concerns, there is increasing awareness on judicious use of natural resources, including water. Large hydroelectric power plants are generally multi-purpose projects and require huge quantities of water for their operation. Usually the generating units in a hydroelectricpower plant are put in operation to meet the electrical load demand without considering the efficiency of the units, which can lead to excessive water use. It is now need of the hour to pay more attention to optimizing the utilization of water in hydroelectric power plants.This paper presents strategic planning for optimal operation of large hydroelectric power plants. Large variation inefficiency of a Francis turbine forms the basis of proposed methodology in which turbines are operated at maximum efficiency. In one approach, discharge is minimized for constant load operation thus conserving water. In another approach, generation is maximized with the same quantity of water. The fringe benefits include creation of operating reserve and availability of additional reactive power in the generator. DOI: http://dx.doi.org/10.3126/hn.v14i0.11266 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014, January Page: 53-58